engaruh Kesesuaian Etika Akademik pada Kepuasan, Komitmen, dan Pindah Kerja - Muhammad Syafruddin (Jurnal Akuntansi dan Bisnis, 2005)
This study examines the influence of ethical fit on educator’s attitudes and intentions to turnover. The results of this investigation provide support for the conjecture that ethical work climate is an important variable in the study of person-organization fit. Ethical fit was found to be significantly related to turnover intentions, continuance commitment, and affective commitment, but not to job satisfaction. Results are discussed in regard to some of affective and cognitive distinction among satisfaction, commitment, and behavioral intentions.